Improving the Use of Learning Media through the Development of E-Storybooks for Fifth-Grade Students - Pitaloka, Ni Putu Riza Clarita; Suprianti, G.A.P; Wahyuni, Luh Gede Eka (Journal of Education Technology, 2024)
The availability of supplementary materials in learning needs to be improved. Due to the change in curriculum, it was difficult for teachers to prepared materials so that they only rely on textbooks. Therefore, this research was conducted on the development of e-storybooks integrated with the Merdeka Curriculum for fifth-grade students. This research aimed to produced e-storybooks that were interactive, innovative, interested and integrated with the Curriculum. Design and Development (D&D) model used in this research which included four stages namely Analysis, Design, Development, and Evaluation, which combined with qualitative and quantitative methods. First, learning problems, teacher and students’ interviews, and document were analyzed. Second, it continued with the development of blueprints related to the developed topics and then the creation of product layouts. The third stage, the e-storybooks were developed by Canva and Book Creator, then revised according to the experts’ feedback and judged by experts. The last stage, conducted product trial, interviews, and product quality judgment which involved teacher and students. This research resulted e-storybooks that were maximally beneficial, being useful as good alternative learning media for language learning, vocabulary development and interested learning experienced for students. Through the results of this study, e-storybooks can be a new alternative as supplementary materials to support learning so that teachers should maximize the use of supplementary materials that are integrated with the curriculum and technology.